Hormonal determinants of the severity of andropausal and depressive symptoms in middle-aged and elderly men with prediabetes - Rabijewski, Michał (Clin Interv Aging, 2015)
Andropausal and depressive symptoms are common in aging males and may be associated with hormone deficiency. We investigated the severity of andropausal and depressive symptoms, as well as their hormonal determinants, in 196 middle-aged and elderly men (age range: 40–80 years) with prediabetes (PD) and in 184 healthy peers. PD was diagnosed according to the definition of the American Diabetes Association. The severity of andropausal and depressive symptoms was assessed using the Aging Males’ Symptoms Rating Scale and the Self-Rating Depression Scale. Total testosterone (TT), calculated free testosterone (cFT), dehydroepiandrosterone sulfate (DHEAS), and insulin-like growth factor 1 (IGF-1) were measured. The prevalence of andropausal syndrome in men with PD was significantly higher than that in healthy men (35% vs 11%, respectively). In men with PD aged 40–59 years, the severity of sexual, psychological, and all andropausal symptoms was greater than in healthy peers, while in elderly men (60–80 years), only the severity of psychological symptoms was greater than in healthy peers. The severity of depressive symptoms in the middle-aged men with PD was greater than in healthy peers, while the severity of depressive symptoms in elderly men with PD and healthy peers was similar. The higher prevalence of andropausal symptoms was independently associated with cFT and IGF-1 in middle-aged men and with TT and DHEAS in elderly men with PD. The more severe depression symptoms were associated with low TT and DHEAS in middle-aged men and with low cFT and DHEAS in elderly men with PD. In conclusion, the prevalence of andropausal symptoms, especially psychological, was higher in prediabetic patients as compared to healthy men, while the severity of depressive symptoms was higher only in middle-aged men with PD. Hormonal determinants of andropausal and depressive symptoms are different in middle-aged and elderly patients, but endocrine tests are necessary in all men with PD.